Hydrogen production by microwave based plasma dissociation of water. (15th March 2020) - Chehade, Ghassan; Lytle, Spencer; Ishaq, Haris; Dincer, Ibrahim
Abstract: In this study, we propose a new method to dissociate water vapor into hydrogen gas by microwave generated plasma. In one stage, steam flows by direct discharge into a custom developed reactor inside the 900 W microwave. The high energetic electrons produced by electric field acceleration of 2.45 GHz microwave collide with water vapor molecules, these molecules are ionized and dissociated into hydrogen and oxygen radicals. The concentration of hydrogen gas is found between 2500 and 8000 PPM. Also, the energy and exergy efficiencies fall below 10% to one another, where the energy efficiency ranges between 11.6% and 53.7% throughout the experiments. From these results, this study demonstrates a unique method of hydrogen production via water plasmolysis and investigates the energy and exergy efficiencies for applications involving the collection of hydrogen gas as an alternative fuel source.